Comparison of interfacial and electrical properties between Al2O3 and ZnO as interface passivation layer of GaAs MOS device with HfTiO gate dielectric*Project supported by the National Natural Science Foundation of China (Nos. 61176100, 61274112). (March 2015) - Zhu, Shuyan; Xu, Jingping; Wang, Lisheng; Huang, Yuan; Tang, Wing Man
Abstract GaAs metal-oxide-semiconductor (MOS) capacitors with HfTiO as the gate dielectric and Al2O3 or ZnO as the interface passivation layer (IPL) are fabricated. X-ray photoelectron spectroscopy reveals that the Al2O3 IPL is more effective in suppressing the formation of native oxides and As diffusion than the ZnO IPL. Consequently, experimental results show that the device with Al2O3 IPL exhibits better interfacial and electrical properties than the device with ZnO IPL: lower interface-state density (7.2 × 1012 eV−1 cm−2), lower leakage current density (3.60 × 10−7 A/cm2 at Vg = 1 V) and good C−V behavior.